Better health indicators of FitSpirit participants meeting 24-h movement guidelines for Canadian children and youth. (28th October 2020) - Guimarães, Roseane de Fátima; Gilbert, Jo-Anne; Lemoyne, Jean; Mathieu, Marie-Eve
Summary: This study aims to determine the proportion of girls who meet the recommendations for moderate-to-vigorous physical activity (MVPA), screen time and sleep duration among FitSpirit participants and evaluate the associations of these recommendations with perceived health-related quality of life (QOL), perceived health, physical activity (PA), self-efficacy and body mass index. Cross-sectional analyses of FitSpirit data were performed. All variables were collected through an online questionnaire. The proportion of girls meeting all recommendations was 2.2%, while 72.5% met either one or two and 25.4% met none. A greater percentage of girls with ≥3 years in FitSpirit met MVPA and sleep recommendations combined when compared with fewer years (12.9% vs. 1.7% with 1 year; vs. 10.1% with 2 years; p  < 0.05). Meeting the combinations of MVPA and screen time ( β  = 0.19, 95% CI = 0.40, 1.68), MVPA and sleep ( β  = 0.20, 95% CI = 0.27, 1.04) and all three combined ( β  = 0.17, 95% CI = 0.33, 1.71) was the most significant predictors of better perceived QOL. Respecting MVPA recommendations predicted a better perceived health ( β  = 0.18, 95% CI = 0.18, 0.87) while girls who slept as recommended had a better PA-related self-efficacy ( β  = 0.23, 95% CI = 0.51, 2.11). Not meeting any recommendation was associated with inferior PA-related self-efficacy ( β  = −0.32, 95% CI = −3.03, −1.21). Lastly, meeting MVPA and sleep recommendations was significantly associated with lower body mass index z -scores ( β  = −0.14, 95% CI = −1.16, −0.11). There was a small percentage of girls following all of the recommendations. Furthermore, meeting individual and combined recommendations was associated with better perceived QOL and health, PA self-efficacy as well as healthier body mass index z -score.